2017
DOI: 10.1186/s12967-017-1153-4
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic strategies for cell-based neovascularization in critical limb ischemia

Abstract: Critical limb ischemia (CLI) causes severe ischemic rest pain, ulcer, and gangrene in the lower limbs. In spite of angioplasty and surgery, CLI patients without suitable artery inflow or enough vascular bed in the lesions are often forced to undergo amputation of a major limb. Cell-based therapeutic angiogenesis has the potential to treat ischemic lesions by promoting the formation of collateral vessel networks and the vascular bed. Peripheral blood mononuclear cells and bone marrow-derived mononuclear cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 96 publications
0
37
0
Order By: Relevance
“…The potential of stem cells has been explored to overcome limitations of conventional revascularization methods such as PTA and bypass surgery (4, 5, 9). SVF cells consist of a heterogeneous population of cells, including adipose stromal, hematopoietic stem, progenitor, and endothelial cells (15).…”
Section: Discussionmentioning
confidence: 99%
“…The potential of stem cells has been explored to overcome limitations of conventional revascularization methods such as PTA and bypass surgery (4, 5, 9). SVF cells consist of a heterogeneous population of cells, including adipose stromal, hematopoietic stem, progenitor, and endothelial cells (15).…”
Section: Discussionmentioning
confidence: 99%
“…Critical limb ischemia is characterized by markedly reduced blood flow to the extremities and is the most severe and frequent form of peripheral artery disease. Cell therapy represents a promising therapeutic approach for vascular tissue regeneration for ischemic diseases [ 67 ]. However, clinical trials indicate consistently modest long-term improvements due, at least in part, to poor survival of transplanted cells [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, there is a clear disparity between pre-clinical trials and large randomized control trials. Few clinical trials report long-term positive effects or clinically significant results ( 18 , 41 ). These disappointing findings with current angiogenic agents can be attributed to numerous factors, including suboptimal delivery strategies ( 42 ), disease mediated dysfunction ( 43 ), methodological differences, and pre-clinical models which lack common CLI risk factors ( 41 ).…”
Section: Therapeutic Potential Of Angiogenic Factorsmentioning
confidence: 99%
“…Angiogenic agents, such as gene or cell therapy, have been the focus of investigation, with the aim of inducing a pro-angiogenic milieu in the affected ischemic limb. Regrettably, the results from clinical trials using such agents have shown little clinical benefit regarding primary outcome measures (i.e., patency, amputation-free survival, major limb adverse effects) ( 18 – 20 ). This highlights both the complexity of therapeutic angiogenesis and the need to develop new agents for the management of CLI.…”
Section: Introductionmentioning
confidence: 99%